MODIFIKASI SYARIAH PADA KERANGKA RISIKO DAN RETURN - Saputra, Andrian - (IJMA (Indonesian Journal of Management and Accounting), 2024)
This article discusses risk and return which is a form of sharia modification in sharia financial management. The modification in question is an innovative step that is being pursued financially. The aim of this research is to understand risk and return as an inseparable part of the presence of modifications in finance, especially when viewed from a sharia perspective. Refers to modifications of sharia where Islamic law is conceptualized in it. So, there are differences in the form of mechanisms for risk and return. The difference in question is from conventional to sharia. This happens because there is no such thing as a risk-free investment opportunity. Risk and return are very closely related because the differences between the two cannot be separated. Return and risk are clearly analogous to the greater the risk, the greater the return that should be compensated. Conversely, the smaller the return value, the smaller the level of risk that must be considered. That is why risk and return are said to be in the same direction, in harmony and in one direction so that they cannot be separated in the sharia modification framework.